2018
DOI: 10.1021/acs.inorgchem.8b02681
|View full text |Cite
|
Sign up to set email alerts
|

Lanthanide-Based Coordination Polymers With 1,4-Carboxyphenylboronic Ligand: Multiemissive Compounds for Multisensitive Luminescent Thermometric Probes

Abstract: Reactions in water of lanthanide chlorides with the sodium salt of 1,4-carboxyphenylboronic acid lead to two series of isostructural compounds with respective general chemical formulas [Ln­(cpb)3(H2O)2]∞ for Ln = La or Ce and [Ln­(cpbOH)­(H2O)2·(cpb)]∞ for Ln = Pr–Lu (except Pm) plus Y. Heterolanthanide coordination polymers that are isostructural to the second series have been synthesized, and their photophysical properties have been studied. This study evidences that it is possible to design multiemissive la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
45
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 71 publications
1
45
0
Order By: Relevance
“…This was expected because a PET mechanism, which is observed for the Eu-based homo-lanthanide coordination polymer is highly temperature dependent 66 and it has been shown that inter-metallic energy transfer are strongly temperature dependent. 63…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This was expected because a PET mechanism, which is observed for the Eu-based homo-lanthanide coordination polymer is highly temperature dependent 66 and it has been shown that inter-metallic energy transfer are strongly temperature dependent. 63…”
mentioning
confidence: 99%
“…Simplified Jablonsky and Dieke diagrams for lanthanide ions 63. S = singlet, T = triplet, ILCT = intra-ligand charge transfer, ISC = intersystem crossing, ET = energy-transfer.…”
mentioning
confidence: 99%
“…On the basis of their powder diffraction diagram, these molecular alloys have all been assumed to be isostructural to [Tb(cpbOH)] ∞ . 51 Relative contents of the different lanthanides in the coordination polymers have been estimated by Energy Dispersive Spectroscopy (Table S2). On the basis of their powder diffraction diagrams, these core-shell compounds have all been assumed to be isostructural to [Tb(cpbOH)] ∞ .…”
Section: Synthesis Of the Micro-crystalline Powders Of Homo-lanthanidmentioning
confidence: 99%
“…The use of lanthanide compounds as thermal probes was recently and exhaustively reviewed by Carlos and co‐workers . Among these sensors, Eu 3+ ‐based luminescent complexes have been widely investigated to be used as molecular thermometers over conventional thermometers . The Eu 3+ luminescence is affected by temperature and can be monitored by the induced changes in the integrated emission intensity of a single transition, a pair of transitions, spectral shifts, the band shape or bandwidth of a certain transition and lifetime.…”
Section: Introductionmentioning
confidence: 99%
“…[1,2] Among these sensors, Eu 3 + -based luminescent complexes have been widely investigated to be used as molecular thermometers over conventional thermometers. [3][4][5][6][7][8] The Eu 3 + luminescence is affected by temperature and can be monitored by the induced changes in the integrated emission intensity of a single transition, a pair of transitions, spectral shifts, the band shape or bandwidth of a certain transition and lifetime. This topic has been widely explored since 2010, mainly due to the enormous importance of luminescence thermometry in nanotechnology and nanomedicine [9,10,11,12] Eu(tta) 3 complex (tta = 3-thenoyltrifluoroacetonate) was presented as the first example with realtime thermogenesis in a single HeLa cell, with temperature variations as low as 1°C, when dissolved in DMSO.…”
Section: Introductionmentioning
confidence: 99%